Intrauterine contraceptive device embedded in the omentum – case report - Zolnierczyk P; Cendrowski K; Sawicki W (Dove Medical Press, 2015)
Piotr Zolnierczyk, Krzysztof Cendrowski, Wlodzimierz Sawicki Department of Obstetrics, Gynecology and Oncology, 2nd Faculty of Medicine, Medical University of Warsaw, Warsaw, Poland Abstract: This report describes the case of a 29-year-old patient, female (nulliparous) who had an intrauterine device (IUD) inserted in 2010 and who has had no gynecological control since then (for 4 years). After this time, the asymptomatic patient had a gynecological appointment, during which a doctor did not find the strings of IUD in the speculum. Ultrasound examination did not reveal the presence of the IUD in the uterine cavity, which led to the suspicion of its presence outside the uterus. The patient was referred to a hospital, where she underwent ultrasound and X-ray examination of the pelvis that confirmed the presence of the IUD outside the uterus. Laparoscopy was performed during which the IUD was localized as being embedded in the omentum. It was removed by performing a resection of a part of the omentum with inflammatory infiltration. The patient was discharged home on the second postoperative day in a good condition. This case confirms the need for gynecological control and ultrasound examination shortly after insertion. An ultrasound or/and X-ray is mandatory in any case of absence of IUD strings previously visible in the vagina, if the patient did not observe its expulsion. Keywords: intrauterine device, myometrium, IUD threads, uterine cavity, ultrasound examination